Sustainable Reindeer Husbandry - Jernsletten, Johnny-Leo L.; Klokov, Konstantin B. (2002)
The goal of the project is to assess circumpolar reindeer herding and husbandry in relation to ecological, economic and social/cultural sustainability. This will be done by carrying out a thematic survey and assessment of reindeer husbandry in the region, with reference to management of pasture land, internal organization and socio-economic conditions in reindeer husbandry.